A review on multimedia communications cryptography - Salem, Yasser; Abomhara, Mohamed; Khalifa, Othman Omran; Zaidan, Aos Alaa; Zaidan, Bilal Bahaa (Academic Journals Inc., 2011)
Now-a-days, Due to the repaid increasing and continuous use of multimedia communications on the internet, Security is becoming more and more relevant and important. However, special and reliable security is required for the many multimedia applications available such as video conferencing, digital television and mobile TV. The classical techniques of data security are not appropriate for the current multimedia usage. This study will presents the currently algorithm of multimedia encryption schemes that have been proposed in the literature and description the effectiveness of the multimedia security. It is a comparative study between symmetric key encryption and asymmetric key encryption in achieving an efficient, flexible and secure video data